Phenolic compounds, organic acids profiles and antioxidative properties of beefsteak fungus (Fistulina hepatica) - Ribeiro, Bárbara (2007)
The phenolic compounds and the organic acids composition of the edible beefsteak fungus Fistulina hepatica was determined by HPLC/DAD and HPLC/UV, respectively. The results showed a profile composed by five phenolic compounds (caffeic, p-coumaric and ellagic acids, hyperoside and quercetin) and six organic acids (oxalic, aconitic, citric, malic, ascorbic and fumaric acids). The quantification of the identified compounds revealed that ellagic acid (ca. 49.7%) and malic acid (ca. 57.9%) are the main compounds in this species. In a general way the phenolic profile revealed to be more constant than the organic acids one and could be more useful for the quality control of the species. Beefsteak fungus was also investigated for its capacity to act as a scavenger of DPPH- radical and reactive oxygen species (superoxide radical, hydroxyl radical and hypochlorous acid). Good results were obtained against DPPH in a concentration-dependent manner. Beefsteak fungus also displayed good activity against superoxide radical, achieved by its capacity to act as both scavenger and xanthine oxidase inhibitor. A prooxidant effect was noticed for hydroxyl radical, which may be due to its capacity for iron ions reduction. Little ability for iron chelation was also observed. Beefsteak fungus showed a weak protective effect against hypochlorous acid.